NPR's podcast start up guide :Create, launch, and grow a podcast on any budget - Weldon, Glen, 1968- (California, Ten Speed Press, 2021)
"From NPR comes the definitive guide to podcasting--featuring step-by-step advice on how to find a unique topic, tell the best stories, and engage the most listeners, as well as the secrets that will take your pod to the next level"--
Keywords: Podcast; Start up Guide